Eastern Mediterranean Area in Energy Security of The European Union: From Sea Border Issues to Economic Conflicts of Interest - Tutar, Hasan; Sarkhanov, Teymur; Guliyeva, Nigar (International Journal of Energy Economics and Policy, 2022)
The interdependence experienced on a global scale today has gained more importance with the increasing demand for energy resources. The situation of interdependence may cause various conflicts due to the differences in strategy between countries regarding access to energy resources. In this destructive competitive environment, hydrocarbons, especially natural gas, continue to be an essential means of competition as a strategic energy source. This situation makes the European Union and the countries that are the suppliers of the energy demand of the Union and the transition countries dependent on each other. This situation of interdependence makes energy resources the most important policy tool. Russia, one of the energy suppliers of European states, uses this advantage as an essential political pressure tool. European Union countries turn to alternative resources and areas to reduce dependency in the face of this situation. In recent years, the Eastern Mediterranean basin has been added to these areas. With the discovery of significant hydrocarbon resources in the Eastern Mediterranean, the importance of this region for European countries is increasing. However, this situation causes maritime border disputes and geopolitical conflicts between the countries of the region. This conceptual study emphasizes the solution of problems related to cross-border hydrocarbon resources and the extent to which natural gas reserves in the Eastern Mediterranean will be an alternative to Russian natural gas.